2017
DOI: 10.1080/03007995.2017.1407303
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review and network meta-analysis of cladribine tablets versus alternative disease-modifying treatments for relapsing–remitting multiple sclerosis

Abstract: In this first NMA to consider cladribine tablets, ocrelizumab and daclizumab for treatment of RRMS, cladribine tablets are a comparatively effective and safe alternative to other DMTs in both active RRMS and HRA + DAT populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 56 publications
2
85
0
2
Order By: Relevance
“…However, their inclusion would have been complicated and most likely given unreliable results, as there are no direct randomised comparisons between cladribine tablets, fingolimod and natalizumab. However, cladribine tablets have demonstrated a comparable efficacy with other DMDs for highly active disease in recent indirect comparison analyses [50][51][52]. Thus, speculatively, the inclusion of treatment effects could have even increased the affordability of cladribine tablets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their inclusion would have been complicated and most likely given unreliable results, as there are no direct randomised comparisons between cladribine tablets, fingolimod and natalizumab. However, cladribine tablets have demonstrated a comparable efficacy with other DMDs for highly active disease in recent indirect comparison analyses [50][51][52]. Thus, speculatively, the inclusion of treatment effects could have even increased the affordability of cladribine tablets.…”
Section: Discussionmentioning
confidence: 99%
“…In systematic reviews, indirect comparisons, health economic analyses and models, systematic reporting is especially important [21,50]. PICO is commonly applied in, e.g., evidence synthesis and Finnish current care treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of such a trial, network meta-analyses (NMAs) can be used to compare treatments using both direct comparisons of interventions within clinical trials and indirect comparisons based on a common comparator, often placebo (Li et al, 2011). Several such NMAs have compared the different DMTs for RMS (Fogarty et al, 2016;Huisman et al, 2017;Institute for Clinical and Economic Review, 2017;Tolley et al, 2015;Tramacere et al, 2015;Tsivgoulis et al, 2015;Siddiqui et al, 2017;Melendez-Torres et al, 2017). However, these NMAs have used differing methodologies, have not used all available data by combining hazard ratio and count data, (Watkins, 2018) and did not consider the trade-off between efficacy and safety with surface under the cumulative ranking curve (SUCRA) values.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with alemtuzumab, cladribine was a less cost-effective option. 7 An extended analysis of data from the CLARITY trial also revealed that use of cladribine had a significant positive impact on quality of life indices. 8 …”
Section: Evidencementioning
confidence: 99%
“…However, this was not statistically significant. 7 On assessment of cost-effectiveness, cladribine was found to be more cost effective and cheaper than daclizumab, fingolimod and natalizumab in the relevant subgroups with severe disease. Compared with alemtuzumab, cladribine was a less cost-effective option.…”
Section: Evidencementioning
confidence: 99%